Constructing physical injury as routine in the sport of cycling - Albert, E. (1998)
The sport of cycling carries with it significant risks of bodily injury. In the US alone, cycling is estimated to be related to 900 deaths, 20,000 hospital admissions and 580,000 emergency room visits in 1996. This research began by asking how, given the objective risks participants confront, do cyclists deal with the danger. Using data gathered from interviews with riders who defined themselves as serious recreational or racing cyclists, extensive participant observation, personal accounts of cycling accidents posted on several Internet web sites, and content analysis of accident related items found in US cycling publications, riders were observed to engage in patterns of talk and behaviour that functioned to reaffirm what were seen to be central subcultural values related to the primacy of participation regardless of the risks, and to its correlate embodiement in the expression of a desire to return to participation following injury. Observed to specifically not attend to the degree to which risk and injury was an omnipresent feature of their talk, cyclists were found, nonetheless, to routinely engage in practices which served to minimise their actual exposure to risk-filled situations, defuse the perceived threat posed by close calls and accidents by treating them ironically and embedding them as expected and ongoing features of subcultural interactions, and treat the actual occurence and results of cycling crashes as normally expected signs of membership that, over time, are routinely used to chronicle one's career in sport. (Abstract from the British Sociological Association Annual Conference, Edinburgh, April 6-7th, 1998)